Prevalence of sleep disordered breathing symptoms among Malay school children in a primary school in Malaysia - Abdullah, Ahmad Fadzil; Ab Rahman, Jamalludin; A W, Norrashidah; M Z, Norzila; K Kassim, Asiah; Awang, Rus Anida; A L, Hasniah; Z, Ramli; H, Samsinah (Malaysian Medical Association, 2012)
Sleep disordered breathing (SDB) is increasingly being diagnosed in children. However, there is no prevalence study done in Malaysia. The study objective was to evaluate the prevalence of SDB symptoms based on parental reports and associated risk factors among Malay school children aged 6 to 10 years old in a primary school using a translated University Michigan Paediatric Sleep Questionnaire (Malay UM-PSQ). The children whose parents responded to the questionnaire and consented were examined, documenting height, weight, skin fold thickness, neck and abdominal circumference, tonsillar size, nostril examination and presence of micrognathia or retrognathia. There were 550 respondents. The prevalence of parental report of SDB symptoms was 14.9 % (95 % CI 11.9, 17.9). Two hundred and eighty-five (51.8%) school children were males with mean age of 8.5 years (SD 1.1). The associated risk factors for SDB symptoms are male, obesity, large neck and waist circumference, positive history of asthma, history of recurrent tonsillitis, enlarged tonsil (> 4+) and enlarged nasal turbinate. Multivariate analysis showed that male gender is the only significant independent risk factor of SDB symptoms